A Handbook for Executive Leadership of Learning and Teaching in Higher Education. - McInnis, Craig; Ramsden, Paul; Maconachie, Don (Office for Learning and Teaching, 2012)
This handbook provides guidance on leadership of learning and teaching for senior university executives. Leadership for learning and teaching increasingly requires specialist skills and knowledge of contemporary approaches to learning and teaching - including familiarity with effective practice in teaching, assessment and the use of technologies to support curriculum delivery - as well as competence in the broader aspects of management and leadership. The handbook meets a widely acknowledged need for a resource to support professional development activities as well as tools for individual leaders. In it, the team attempts to make available ideas and knowledge that are relevant across policy contexts, are useful in the long term, and which take account of, but are not constrained by, current and emerging policy issues related to the student experience. The primary audience for the handbook is provosts, deputy and pro vice-chancellors (including those newly appointed) whose responsibilities centre on the governance and management of teaching and the student experience, as well as those who aspire to such positions. Its focus is on strategic leadership: on an institution's distinctive vision for student learning across subject areas and the means by which the vision can be realised. This handbook is welcome in reminding higher education leaders of their importance in facilitating students' learning and in filling a gap in the literature in describing how leaders may discharge their important role in inspiring excellent teaching and learning.